2019
DOI: 10.1371/journal.pone.0222667
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of prescription in 29 Level 3 Neonatal Wards over a 2-year period (2017-2018). An inventory for future research

Abstract: ObjectivesThe primary objective of this study is to determine the current level of patient medication exposure in Level 3 Neonatal Wards (L3NW). The secondary objective is to evaluate in the first month of life the rate of medication prescription not cited in the Summary of Product Characteristics (SmPC). A database containing all the medication prescriptions is collected as part of a prescription benchmarking program in the L3NW.Material and methodsThe research is a two-year observational cohort study (2017–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…The mean and standard deviation (SD) of the number of drugs per infants received during neonatal care was reported in 14 studies [ 8 , 13 , 18 , 22 , 23 , 24 , 34 , 38 , 43 , 51 , 53 , 63 , 73 , 74 ] and sufficient information was available to impute the SD value in 7 other studies [ 19 , 28 , 32 , 39 , 42 , 69 , 75 ] ( Figure 3 ). The pooled mean (SD) of the number of drugs received per infant, calculated from data reported in 29 studies, was 4 (2.4) drugs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean and standard deviation (SD) of the number of drugs per infants received during neonatal care was reported in 14 studies [ 8 , 13 , 18 , 22 , 23 , 24 , 34 , 38 , 43 , 51 , 53 , 63 , 73 , 74 ] and sufficient information was available to impute the SD value in 7 other studies [ 19 , 28 , 32 , 39 , 42 , 69 , 75 ] ( Figure 3 ). The pooled mean (SD) of the number of drugs received per infant, calculated from data reported in 29 studies, was 4 (2.4) drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies that used the WHO-ATC system, anti-infectives for systemic use were the most frequently prescribed pharmacological group in the majority (14 studies) [ 13 , 23 , 24 , 25 , 30 , 34 , 42 , 43 , 50 , 51 , 59 , 71 , 73 , 76 ]. This was followed by agents for the alimentary tract and metabolism (4 studies) [ 7 , 63 , 65 , 74 ] and agents for the central nervous system (1 study) (32). Among the four studies that listed the pharmacological groups according to their pharmacological class, three studies reported that antimicrobials were the most frequently prescribed group [ 19 , 39 , 47 ] and one study by Ashwin et al (2018) identified that penicillins were the most frequently prescribed [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antibiotics overuse in neonatal wards (NWs) originates from the fear of overwhelming sepsis in an untreated infected baby, the lack of specific clinical and biological signs of neonatal infection, and the difficulty in obtaining efficient routine bacteriological examinations. These factors explain why up to 72% of neonates admitted to NICUs are given antibiotics and why this rate is the highest for the most immature babies, i.e., close to 100% in neonates with extremely low birth weight (ELBW, <1,000 g) or extremely low gestational age (ELGA, <27 weeks) ( Gouyon et al, 2019 ). These high rates are markedly in contrast with the scarcity of proven early-onset neonatal infection (EONI), which has been rated as low as 2.5% in symptomatic ELBW infants in the United States ( Puopolo et al, 2017 ) and at 2.3% in the United Kingdom ( Cailes et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%